The relationship between physical exercise and bioactive compounds in health and disease: a narrative review - Silva, Oyatagan Levy Pimenta da; Moura, Hemeson Lira de; Trindade, Maria Eduarda Flores; Santos Junior, Elson Bezerra dos; Lima, Ildercílio Mota de Souza; Teodoro, Anderson Junger (OBSERVATÓRIO DE LA ECONOMÍA LATINOAMERICANA, 2025)
Nowadays, the quality and diversity of the foods we eat are essential, not only because of their nutritional value, but also because of the important biological activity they perform. In addition to essential nutrients, fruits and vegetables, for example, contain chemical substances that can bring a variety of health benefits. These are known as bioactive compounds. This article aims to present the benefits that physical exercise together with bioactive compounds offers for a better quality of life, both in health and in disease. The methodology used was a narrative review on the subject. The results obtained were that physical exercise and bioactive compounds are recognized for their ability to contribute to reducing the risk of chronic non-communicable diseases, inflammation, cardiovascular problems and other conditions. These beneficial effects are largely linked to the consumption of fruits and vegetables, which perform antioxidant functions and protect organs such as the liver, brain, kidneys and the cardiovascular system. The antioxidant activity of fruits can vary according to their concentrations of vitamin C, carotenoids, flavonoids and other phenolic compounds. Furthermore, they can help reduce the risk of cancer and prevent macular degeneration. Therefore, it can be concluded that the effectiveness of these compounds is linked to their composition and concentration in food. The presence of these substances is directly affected by factors such as environmental conditions, type of agricultural management, stage of maturation and variety of the plant, among other elements.